Penerapan Model Pembelajaran Problem Solving Dalam Meningkatkan Hasil Belajar IPS Siswa SD - Sitti Jauhar; Makmur Nurdin (Universitas Negeri Makassar, 2017)
The problem in this research is the low of IPS learning result of fourth grader of Inpres 3/77 Manurunge Sub District Tanete Riattang Bone Regency. The problem can be formulated as follows